Anemia in rural and urban school children and its correlation with nutritional status in Yogyakarta - A. Samik Wahab A. Samik Wahab (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1985)
A survey on anemia has been conducted on 94 school children in Yogyakarta of whom 46 were from rural and 48 from urban private elementary schools. The subjects ranged in age from 6 to 12 years. The frequency of anemia showed significant difference between the two groups (p < 0.01). The result showed that 39.13% of the rural and 6.25% of the urban school children were anemic. More girls were anemic than boys, namely 13.83% of the girls and 8.5% of the boys (p < 0.05). Amongst the causes of anemia in the rural area is thought to be worm infestation and other factors enhancing iron deficiency. It is suggested that iron supplement to adolescent girls is important. Key Words: anemia - hemoglobin - anthropometric measurement - nutritional status - iron deficiency